The Managerial and Government Ownership Effect on Dividend Policy: The Moderating Role of Investment Opportunities - Abdul Fatah Ismail; Nadia Anridho (Jurnal Dinamika Akuntansi)
Purpose: This study investigates agency conflicts related to dividend policy within corporate companies, focusing on managerial ownership and government ownership.